2007
DOI: 10.1002/pola.22376
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of 1,2,3‐triazole‐cured polymers from endcapped azides and alkynes

Abstract: Fourteen commercial polyols have been characterized by GPC, NMR spectroscopy, and elemental analysis. From these, eight corresponding tosylates, six nitrate esters, seven mesylates, 13 alkynes, and 14 azides have been prepared and all these derivatives have been fully characterized. Five alkyne monomers and eight azide monomers were also prepared. Twelve alkynes and 13 azides (functionality 2–4) were combined in 1,3‐dipolar cycloaddition reactions under neat conditions to prepare triazole‐cured polymers, avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 36 publications
2
59
0
Order By: Relevance
“…Recently, Katritzky et al reported a similar study wherein a library of multifunctional azides and alkynes were polymerized in solution and characterized by standard techniques. [121] Finn and coworkers also utilized two of their previously studied adhesive molecules, tripropargyl amine with 1,6-diazidohexane, in a solution phase CuAAC reaction to yield a highly crosslinked polymer which was observed to reversibly swell and deswell when treated with trifluoroacetic acid due to the amine functionalities within the material (Scheme 22). [122] The authors suggest that the polarity, stability, and p-stacking properties of the triazole products can potentially be exploited for a range of applications, a notion that has been abundantly confirmed by reports that have appeared in the past few years.…”
Section: Small Molecule Covalently Linked Networkmentioning
confidence: 93%
“…Recently, Katritzky et al reported a similar study wherein a library of multifunctional azides and alkynes were polymerized in solution and characterized by standard techniques. [121] Finn and coworkers also utilized two of their previously studied adhesive molecules, tripropargyl amine with 1,6-diazidohexane, in a solution phase CuAAC reaction to yield a highly crosslinked polymer which was observed to reversibly swell and deswell when treated with trifluoroacetic acid due to the amine functionalities within the material (Scheme 22). [122] The authors suggest that the polarity, stability, and p-stacking properties of the triazole products can potentially be exploited for a range of applications, a notion that has been abundantly confirmed by reports that have appeared in the past few years.…”
Section: Small Molecule Covalently Linked Networkmentioning
confidence: 93%
“…[22] 1,10-Diazidodecane 8, [23] 1-azido-2-(2-azidoethoxy) ethane 9 [24] are known compounds and were prepared by the reported methods. Chemicals used -LiAlH 4 , POCl 3 , NaBH 4 , NaH, 80 % solution of propargyl bromide in PhMe, sodium ascorbate, CuSO (4).…”
Section: Methodsmentioning
confidence: 99%
“…The azide group is known to react with propargyl groups by [3+2] cycloaddition reaction, in the presence of catalyst Cu (I) or not, to give 1,2,3-triazole rings [8][9][10][11][12]. The pathway of cycloaddition reaction is presented in Scheme 3.…”
Section: Cycloaddition Reaction Of 3(a-d) Monomersmentioning
confidence: 99%